Radioiodine and thyroid carcinoma: KI prophylaxis in children - Giovannelli, G. (Acta Biomedica Atenei Parmensis, 2004)
The Chernobyl disaster was followed by a large increase in the incidence of thyroid carcinoma in children. It has been proved that KI prophylaxis may prevent such a heavy consequence. Italy has no more nuclear power plants in activity but is surrounded by the several ones of the neighbouring countries; moreover, relevant amounts of nuclear material are still present in the territory. Therefore a nuclear risk is present in Italy as well as in other close countries and a KI prophylaxis should be organized for our children, at least for those living within 200 miles from a possible source of radioiodine pollution. Guidelines concerning KI prophylaxis exist and are internationally shared in their general outlines.Guidelines we recommend for italian children are summarized in part II (“theory”). However, to be timely and effective, KI prophylaxis must be organized long before the nuclear alarm, and the coordination of its several steps needs to be checked through a mock trial.We suggest a model of organization and describe the practical aspects of carrying out a KI prophylaxis for 82.000 subjects aged 0-18 years living in the Province of Parma (Progetto Sperimentale Parma, PSP). The main goal of PSP is to offer a controlled and reliable model of KI prophylaxis,which could be applied in any other area (previous local adjustement), whenever the central or regional Authorities will consider it necessary or desirable.